Synthesis method and application of a multi-component covalent organic framework / MXene hybrid material
Patent Information
- Application Number
- CN202410730500.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-06
AI Technical Summary
多组分COFs框架将促进电子性质的连续调制,尤其框架内羟基电荷诱导效应与杂化效应协同增强了光生载流子分离及电子转移,有效克服了多组分COFs框架内电子回流引起的U(VI)光还原性能差等问题
(1)本发明制备的多组分共价有机框架/Mo2TiC2杂化材料,给电子基团羟基的引入能够降低带隙并诱导多组分COFs内的电荷分离,尤其是与杂化效应协同作用的电荷调控有效抑制了电荷载流子重组,提高了整体光生电子还原U(VI)的能力。
Smart Images

Figure CN118681603B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of environmental protection technology, specifically relating to a method for synthesizing and applying a multi-component covalent organic framework / MXene hybrid material. Background Technology
[0002] Nuclear energy, as a clean and efficient energy source, will play an indispensable role in the future global energy structure. The mining, processing, nuclear fuel cycle, and spent fuel reprocessing of uranium-bearing ore will generate large amounts of radioactive uranium-containing wastewater, causing groundwater pollution and posing a threat to the environment and human health. Photocatalytic reduction of soluble U(VI) to insoluble U(IV) is a promising method, characterized by its greenness, economy, high efficiency, stability, and lack of secondary pollution, which is beneficial to the development of clean and renewable nuclear energy and the resolution of the environmental crisis. However, high photogenerated electron-hole recombination rates, low solar energy utilization rates, and slow semiconductor surface reaction rates are the core bottlenecks restricting photocatalytic activity (S. Li, D. Pan, Z. Cui, Y. Xu, H. Shang, W. Hua, F. Wu, W. Wu, Synergistic effects of oxygen vacancies and heterostructures for visible-light-driven photoreduction of uranium. Sep. Purif. Technol., 2022,301: 121966). Therefore, there is an urgent need to develop photocatalysts to improve the photocatalytic reduction efficiency of U(VI).
[0003] Covalent organic frameworks (COFs) are promising materials for uranium extraction due to their uniform porosity, tunable chemical properties and functional groups, and high specific surface area. Photofunctional COFs, in particular, possess great potential for the photoreduction of U(VI) to U(IV). Scalable π-conjugated frameworks and tunable band gaps facilitate optimization of light trapping and charge separation performance, while ordered crystal structures promote exciton migration and charge transfer (S. Liu, Q. Su, W. Qi, K. Luo, X. Sun, H. Ren, Q. Wu, Highly hydrophilic covalent organic frameworks as efficient and reusable photocatalysts for oxidative coupling of amines in aqueous solution, Catal. Sci. Technol., 2022, 12: 2837-2845). However, rapid electron-hole recombination, transient matter instability, and energy loss during exciton migration significantly reduce the photocatalytic activity of COFs. The strong exciton effect, generated by the electrostatic interaction between photogenerated electrons and holes, is an inherent property of organic photocatalysts and will severely reduce photocatalytic performance in practical applications. To obtain high-performance COF-based photocatalysts, researchers are exploring methods to increase the visible light absorption range, optimize the band structure, overcome the exciton effect, and reduce the recombination of photogenerated electrons and holes (Z. Chen, J. Wang, M. Hao, Y. Xie, X. Liu, H. Yang, GIN Waterhouse, X. Wang, S. Ma, Tuning excited state electronic structure and charge transport in covalentorganic frameworks for enhanced photocatalytic performance, Nat. Commun., 2023, 14(1): 1106.). Since the donor and acceptor generate an electron push-pull effect, establishing a donor (D)-acceptor (A) structure is usually a reliable strategy to promote photocatalytic activity. In the photocatalytic reaction system, COF photocatalysts composed of DA structures are excited by light, causing electrons to migrate from the donor to the electrophilic acceptor, resulting in intermolecular charge transfer, thereby suppressing carrier recombination caused by the strong exciton effect. However, most COF materials are typically made by two-component condensation, which limits the framework structure and functional tuning.Furthermore, the most studied binary-structured COF photocatalysts to date are linked by imines (C=N), whose weak π-electron connectivity significantly affects their photochemical processes and photocatalytic performance, limiting practical applications. Multi-component strategies, on the other hand, are a mature and widely used approach. They introduce multiple functional building blocks into the crystal structure, facilitating precise tuning of COF functions. Multi-component cooperation in multi-component COFs promotes continuous modulation of electronic properties and ultimately enhances the redox capacity of photogenerated charge carriers. On the other hand, introducing various electron-donating groups creates charge-inducing effects that modulate their affinity for active sites and also promote charge separation. The construction of hybrid systems can also effectively separate photogenerated electrons and holes, and suppress electron backflow within multicomponent frameworks, thus avoiding problems such as reduced performance of photocatalytic reduction of U(VI) (H. Yang, M. Hao, Y. Xie, X. Liu, Y. Liu, Z. Chen, X. Wang, GIN Waterhouse, S. Ma, Tuning local charge distribution in multicomponentcovalent organic frameworks for dramatically enhanced photocatalytic uranium extraction, Angew. Chem. Int. Ed. Engl., 2023: e202303129.). Therefore, by leveraging the charge-induced effect of multicomponent COFs and the synergistic effect of hybridization with functional materials to regulate the band gap, improve light absorption efficiency, accelerate carrier transport, and enhance the separation of photogenerated charges, photocatalysts with high photocatalytic activity can be designed to improve their application potential. Summary of the Invention
[0004] This invention aims to provide a method for synthesizing and applying multi-component covalent organic frameworks (COFs) / MXene hybrid materials. Using 2,4,6-tricarboxymethyl phloroglucinol, 5,5'-diamino-2,2'-bipyridine, and an amino monomer as reactants, a multi-component covalent organic framework is prepared via a Schiff base reaction. This framework is then self-assembled with Mo2TiC2MXene to synthesize a multi-component covalent organic framework / Mo2TiC2 hybrid material. The introduction of the negatively charged bimetallic Mo2TiC2MXene not only increases the hydrophilicity of the photocatalyst but also forms an effective interfacial electron transport channel. The multi-component COF framework promotes continuous modulation of electronic properties; in particular, the synergistic enhancement of photogenerated carrier separation and electron transfer through the hydroxyl charge-induced effect and hybridization effect within the framework effectively overcomes the problem of poor U(VI) photoreduction performance caused by electron backflow within the multi-component COF framework. The multi-component covalent organic framework / Mo2TiC2 hybrid material synthesized by the method of this invention has advantages such as low band gap, wide light absorption range, good hydrophilicity, fast electron transfer rate, and strong electron-hole separation. It exhibits fast, efficient, and selective photocatalytic reduction kinetics of U(VI) and has good application prospects.
[0005] To achieve the above objectives, the present invention specifically adopts the following technical solution: This invention provides a method for synthesizing a multi-component covalent organic framework / Mo2TiC2 hybrid material, comprising the following steps: 1) Take 2,4,6-tricarboxymethyl phloroglucinol, 5,5'-diamino-2,2'-bipyridine and amino monomer, add them to the solvent, degas them by freezing-thawing cycle and flame-sealing, and react them at 90-150 °C to obtain a multi-component covalent organic framework; 2) Mo2AlTiC2 and HF were reacted at 40-65 °C. After centrifuging the resulting mixture to remove the viscous precipitate, tetramethylammonium hydroxide was added and stirred to obtain Mo2TiC2MXene nanosheets. 3) Mix the multi-component covalent organic framework obtained in step 1) with the Mo2TiC2MXene obtained in step 2) in a solvent and stir to obtain a multi-component covalent organic framework / Mo2TiC2 hybrid material.
[0006] Further, the amino monomer in step 1) is benzidine or 3,3-dihydroxybenzidine.
[0007] Further, in step 1), the molar ratio of 2,4,6-tricarboxyloylphloroglucinol, 5,5'-diamino-2,2'-bipyridine and amino monomer is 10:7:(4-12).
[0008] Further, the solvent in step 1) is a mixture of mesitylene, 1,4-dioxane and acetic acid, and the volume ratio of mesitylene, 1,4-dioxane and acetic acid is (3-15):(3-5):(2-4).
[0009] Further, in step 3), the mass ratio of the multi-component covalent organic framework to Mo2TiC2MXene is 1:(1-4).
[0010] The present invention also provides the application of the multi-component covalent organic framework / Mo2TiC2 hybrid material synthesized by the above method in the photocatalytic reduction of U(VI).
[0011] This invention also provides the application of the multi-component covalent organic framework / Mo2TiC2 hybrid material synthesized by the above method in the selective removal of U(VI) from rare earth tailings wastewater containing interfering ions, characterized in that the interfering ions include La. 3+ Ce 3+ Pr 3+ 、Nd 3+ 、Sm 3+ Eu 3+ Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3+ Tm 3+ Yb 3+ Lu 3+ Mg 2+ Al 3+ Co 2+ Ni + .
[0012] Compared with the prior art, the beneficial effects of the present invention are: (1) The multi-component covalent organic framework / Mo2TiC2 hybrid material prepared by the present invention can reduce the band gap and induce charge separation in multi-component COFs by introducing the electron-donating hydroxyl group. In particular, the charge regulation that works in synergy with the hybridization effect effectively suppresses charge carrier recombination and improves the overall ability of photogenerated electrons to reduce U(VI).
[0013] (2) The multi-component covalent organic framework / Mo2TiC2 hybrid material prepared by the present invention has the introduction of the negatively charged bimetallic Mo2TiC2MXene on the surface, which not only increases the hydrophilicity of the photocatalyst, but also forms an effective interfacial electron transport channel, accelerating electron transport.
[0014] (3) The multi-component covalent organic framework / Mo2TiC2 hybrid material prepared by the present invention has the advantages of low band gap, wide light absorption range, good hydrophilicity, fast electron transfer rate and strong electron-hole separation.
[0015] (4) The multi-component covalent organic framework / Mo2TiC2 hybrid material prepared by the present invention can photocatalytically reduce U(VI) to U(IV).
[0016] (5) The multi-component covalent organic framework / Mo2TiC2 hybrid material prepared by the present invention has fast photocatalytic reduction kinetics, high efficiency and good selectivity for U(VI), and has good application prospects. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the synthesis route for multi-component covalent organic framework / Mo2TiC2 hybrid materials.
[0018] Figure 2 The images show the PXRD plot of TBD and the XRD plot of the corresponding AA stacked structure (a) and the PXRD plot of TBB and the XRD plot of the corresponding AA stacked structure (b).
[0019] Figure 3 PXRD plots of Mo2TiAlC2, Mo2TiC2, TBD, TBB, TBBM, and TBDM.
[0020] Figure 4 The UV / Vis diffuse reflectance spectra (a) and band gap diagrams (b) are for TBD, TBB, TBBM, and TBDM.
[0021] Figure 5 These are the photocurrent response diagrams for TBD, TBB, TBBM, and TBDM.
[0022] Figure 6 The diagram shows the adsorption isotherms (a) and adsorption kinetics (b) of TBD, TBB, TBBM and TBDM for the photocatalytic reduction of U(VI).
[0023] Figure 7 This is a selectivity diagram of TBDM for the photocatalytic reduction of U(VI).
[0024] Figure 8 The work function graphs of TBD (a) and Mo2TiC2 (b) are calculated using DFT. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with embodiments. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0027] Example 1: Synthesis and Characterization of Multicomponent Covalent Organic Framework / Mo2TiC2 Hybrid Materials 2,4,6-Tricarboxymethyl phloroglucinol (Tp, 10.5 mg, 0.05 mmol), 5,5'-diamino-2,2'-bipyridine (Bpy, 6.5 mg, 0.035 mmol), and 3,3'-dihydroxybenzidine (DHB, 8.6 mg, 0.04 mmol) were added to a Pyrex tube containing a mixed solvent of mesitylene (0.75 mL), 1,4-dioxane (0.25 mL), and acetic acid (0.1 mL, 6 M). The mixture was sonicated for 15 min, degassed by a freeze-thaw cycle, and flame-sealed. The reaction was carried out at 120 °C for 3 days. The solid product was collected, washed repeatedly with anhydrous acetone and methanol, and dried under vacuum at 60 °C to obtain a multicomponent covalent organic framework (TBD) exhibiting hydroxyl-induced charge separation. In addition, a multicomponent covalent organic framework (TBB) was synthesized under the same conditions by replacing 3,3'-dihydroxybenzidine with benzidine (BZ, 7.4 mg, 0.04 mmol).
[0028] Mo2AlTiC2 was slowly added to a polytetrafluoroethylene reactor containing HF, and the mixture was magnetically stirred at 55 °C for 48 h at a speed of 500 rpm. After the reaction, the mixture was poured into a 50 mL centrifuge tube and centrifuged at 8500 rpm 7-8 times, approximately 5 min each time, until a viscous precipitate appeared. To obtain few-layer Mo2TiC2MXene nanosheets, 50 mL of 30 wt% tetramethylammonium hydroxide was added to the above Mo2TiC2 precipitate for intercalation. The mixture was stirred at room temperature with a magnetic stirrer for 24 h, and after repeated centrifugation, few-layer silvery-gray Mo2TiC2MXene was obtained.
[0029] 20 mg of Mo2TiC2MXene was mixed with 10 mg of TBD and TBB respectively, stirred in methanol solution for 2 h, filtered and vacuum dried to obtain multi-component covalent organic framework / Mo2TiC2 hybrid materials TBDM and TBBM.
[0030] Figure 1 This is a schematic diagram of the synthesis route for multi-component covalent organic framework / Mo2TiC2 hybrid materials.
[0031] The crystal structure of the material was characterized by X-ray powder diffraction (PXRD). Figure 2 These are the PXRD plots of TBD and the corresponding simulated XRD plots of the AA stacked structure (a) and (b) of TBB and the corresponding simulated XRD plots of the AA stacked structure. Figure 2 It can be seen that TBD and TBB exhibit sharp diffraction peaks at 3.6° and 3.5°, respectively, corresponding to the (100) crystal plane, indicating that TBD and TBB possess long-range ordered crystal structures. The diffraction peaks of TBD at 6.0° and 13.5° are attributed to the (200) and (210) crystal planes, respectively. Figure 2 a). The diffraction peaks of TBB at 6.1° and 27.5° are attributed to the (200) and (001) planes, with the diffraction peak at 27.5° attributed to the π-π stacking between different layers (a). Figure 2 b). PXRD plots of TBD and TBB were simulated using Material Studio, and the results showed that they both matched the AA stacking pattern.
[0032] Figure 3 PXRD patterns of Mo2TiAlC2, Mo2TiC2, TBD, TBB, TBBM, and TBDM. (Source: [Insert PXRD diagram here]) Figure 3 As can be seen, in the PXRD patterns of Mo2TiC2, TBD, TBB, TBBM, and TBDM, the peak at 39.8° at which the Al crystal plane peak at Mo2TiAlC2 is located disappears. Compared with Mo2TiAlC2, the (002) crystal plane peak of Mo2TiC2 shifts to the left, indicating that the intercalation of solvent molecules expands the interlayer spacing of Mo2TiC2. Furthermore, after bimetallic Mo2TiC2 is hybridized with multi-component COF, the diffraction peak of COF at ~3.5° can still be observed, and the typical small-angle diffraction peak of Mo2TiC2 does not change significantly, indicating that the crystal structure of the synthesized material remains intact during the hybridization process.
[0033] Figure 4 These are the UV / Vis diffuse reflectance spectra (a) and band gap diagrams (b) for TBD, TBB, TBBM, and TBDM. Figure 4 As can be seen, the absorption edge of TBB is 733 nm, while the absorption edge of TBD redshifts to 902 nm after the introduction of hydroxyl groups. This indicates that TBD can not only effectively utilize visible light but also extend it into the near-infrared region, greatly enhancing light utilization. This can be attributed to the significant promotion of electron delocalization within the TBD framework by the introduction of the electron-donating hydroxyl group. Furthermore, the light absorption capability of the prepared hybrid material is further enhanced after hybridization with Mo2TiC2MXene. The band gaps of TBD, TBDM, TBB, and TBBM were calculated using the Kubelka-Munk function. Figure 4As can be seen from b, the introduction of hydroxyl groups significantly reduced the band gap of TBD, from 1.99 eV to 1.76 eV. After hybridization with Mo2TiC2MXene, the band gap of TBDM shifted to 1.71 eV. These results indicate that the synergistic effect of hydroxyl-induced charge separation and hybridization gives TBDM stronger electronic transition capabilities and higher solar energy utilization.
[0034] Figure 5 These are the photocurrent response diagrams for TBD, TBB, TBBM, and TBDM. The transient photocurrent response further verifies the superiority of the synergistic effect of hydroxyl-induced charge separation and hybridization. Figure 5 It is evident that TBDM exhibits the strongest photocurrent, and the photocurrent of TBD is significantly higher than that of TBB. This indicates that the hydroxyl-induced charge separation effect and the hybrid system synergistically regulate charge separation, effectively enhancing the photoreduction ability of U(VI).
[0035] Example 2: Photocatalytic reduction of U(VI) by multi-component covalent organic framework / Mo2TiC2 hybrid material Add 5 mg TBDM to 20 mL of UO2 containing different initial concentrations. 2+ The solution was prepared in an aqueous solution of 20–800 ppm. After shaking at 150 rpm to reach adsorption-desorption equilibrium, the suspension was irradiated with a 300 W xenon lamp for 6 h. The supernatant was then collected and filtered through a 0.22 µm nylon membrane. The concentration of U(VI) remaining in the filtrate was determined by ICP-MS. Figure 6 The figures (a) and (b) show the adsorption isotherms (and kinetics) of TBD, TBB, TBBM, and TBDM for the photocatalytic reduction of U(VI). Figure 6 As can be seen, the maximum adsorption capacity of TBDM for U(VI) under light conditions is as high as 1723.3 mg / g, which is 2.3 times that under dark conditions and far exceeds the adsorption capacity of TBDM for U(VI) under light conditions (1318.9 mg / g). These results indicate that the introduction of hydroxyl groups can effectively promote charge separation within the framework, and in synergy with the hybridization effect, can greatly enhance the adsorption of U(VI).
[0036] At pH 5, 10 mg TBDM was dispersed in 40 mL of a U(VI) solution containing 30 ppm. After shaking the suspension to reach adsorption-desorption equilibrium, it was irradiated with a xenon lamp (300 W) and shaken for the expected contact times (10, 30, 60, 90, 120, 240 min). Approximately 0.5 mL of the sample was taken, filtered through a 0.22 µm membrane, and the remaining U(VI) concentration in the filtrate was determined by ICP-MS. A pseudo-first-order model (-ln(C / C0)=k) was used to evaluate the photocatalytic reaction rate constant k of the photocatalyst, where C0 and C represent the initial and equilibrium concentrations of U(VI), respectively, and k represents the photocatalytic reaction rate constant. Figure 6 As can be seen from b, the photocatalytic reaction rate constant k follows the following order: TBDM (0.0341 min) −1 >TBBM (0.0153min) −1 > TBD (0.0107 min) −1 > TBB (0.0079 min) −1 This efficient kinetics is attributed to the introduction of hydrophilic Mo2TiC2MXene and hydroxyl groups, which reduces the hydrophobicity of the material and facilitates the capture of U(VI). Furthermore, TBDM achieved a U(VI) removal rate of 94.8% after 1 hour of illumination, higher than several other synthesized materials, indicating that TBDM possesses highly efficient photocatalytic activity.
[0037] Example 3: Study on the selectivity of TBDM for U(VI) and the mechanism of electron flow direction At pH=5, uranyl ions react with interfering ions (La) in rare earth tailings wastewater. 3+ Ce 3+ Pr 3+ 、Nd 3+ 、Sm 3+ Eu 3 + Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3+ Tm 3+ Yb 3+ Lu 3+ Mg 2+ Al 3+ Co 2+ Ni +The effect of TBDM on the selective reduction of U(VI) under light was investigated at a concentration ratio of 1:5. 5 mg of TBDM material was dispersed in 20 mL of a solution containing 30 ppm U(VI), shaken at 150 rpm for 6 h, and after standing, the supernatant was collected and filtered through a 0.22 μm membrane. The residual concentration of U(VI) in the solution was determined by ICP-MS.
[0038] Figure 7 This is a selectivity diagram for the photocatalytic reduction of U(VI) by TBDM. (From...) Figure 7 It is evident that even with the coexistence of multiple interfering ions, TBDM still achieved a removal rate of 95.1% for U(VI), indicating that TBDM exhibits excellent selectivity for U(VI) removal.
[0039] To determine the direction of electron flow in the hybrid system, the work functions of TBD(001) and Mo2TiC2(001) were calculated using DFT. Figure 8 These are the work function graphs of TBD (a) and Mo2TiC2 (b) calculated using DFT. Figure 8 As can be seen, the work functions of TBD and Mo2TiC2 are 4.99 and 6.83 eV, respectively. This indicates that under illumination, when Mo2TiC2 and TBD are in close contact, TBD can be excited to generate holes and electrons, and then electrons flow from TBD to Mo2TiC2. The interfacial channels generated by the interaction between the electron clouds of TBD and Mo2TiC2 will accelerate the photoelectron transfer between Mo2TiC2 and TBD.
[0040] The embodiments described above are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they are not intended to limit the present invention. It should be noted that various changes and modifications can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the concept and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. The application of a multi-component covalent organic framework / Mo2TiC2 hybrid material in the photocatalytic reduction of U(VI), characterized in that: The synthesis method of the multi-component covalent organic framework / Mo2TiC2 hybrid material includes the following steps: 1) Take 2,4,6-tricarboxymethyl phloroglucinol, 5,5'-diamino-2,2'-bipyridine and an amino monomer, add them to a solvent, degas by freezing-thawing cycle and flame-sealing, and react at 90-150 °C to obtain a multi-component covalent organic framework; the amino monomer is benzidine or 3,3-dihydroxybenzidine; 2) Mo2AlTiC2 and HF were reacted at 40-65 °C. After centrifuging the resulting mixture to remove the viscous precipitate, tetramethylammonium hydroxide was added and stirred to obtain Mo2TiC2MXene nanosheets. 3) Mix the multi-component covalent organic framework obtained in step 1) with the Mo2TiC2MXene obtained in step 2) in a solvent and stir to obtain a multi-component covalent organic framework / Mo2TiC2 hybrid material.
2. The application according to claim 1, characterized in that, In step 1), the molar ratio of 2,4,6-tricarboxyloyl phloroglucinol, 5,5'-diamino-2,2'-bipyridine, and the amino monomer is 10:7:(4-12).
3. The application according to claim 1, characterized in that, Step 1) The solvent is a mixture of mesitylene, 1,4-dioxane and acetic acid, with a volume ratio of (3-15):(3-5):(2-4).
4. The application according to claim 1, characterized in that, Step 3) The mass ratio of the multi-component covalent organic framework to Mo2TiC2MXene is 1:(1-4).
5. The application according to claim 1, characterized in that, The application of the multi-component covalent organic framework / Mo2TiC2 hybrid material in the selective removal of U(VI) from rare earth tailings wastewater containing interfering ions, including La. 3+ Ce 3+ Pr 3 + 、Nd 3+ 、Sm 3+ Eu 3+ Gd 3+ 、Tb 3+ Dy 3+ Ho 3+ Er 3+ Tm 3+ Yb 3+ Lu 3+ Mg 2+ Al 3+ Co 2+ Ni 2+ .
Citation Information
Patent Citations
Preparation method and use method of two-dimensional sheet layer material modified MXene / TiO2 composite material
CN110433834A
COF-TpBpy-coated VNbC composite photocatalyst and preparation method thereof
CN117482991A
Covalent organic framework films, methods and uses thereof
CN118019575A
